TESL Undergraduates’ Ability to Handle Academic Text-types at University Malaysia Sarawak - Ting, University Malaysia Sarawak, Su-Hie; Tee, KDU College Penang, Malaysia, Pei Feng (Asiatic: IIUM Journal of English Language and Literature, 2008)
This case study examined the ability of TESL undergraduates to handle five text-types commonly required by their assignments, with a specific focus on the structure and language features significant to the text-type. Stratified random sampling was used to obtain 60 coursework assignments across five text-types from undergraduates in the Teaching of English as a Second Language (TESL) degree programme at University Malaysia Sarawak: argument, explanation, discussion, instruction and information report. Genre analysis of the assignments using the frameworks of Feez and Derewianka showed that the information report and explanation text-types were the most difficult in terms of the generic structure.The results showed that the undergraduates were familiar with the staging of argument and discussion but the ideas were sometimes not effectively developed within the stages. The analysis of linguistic choices indicated good use of relevant language features to fulfil the purpose of the text-type in 27 assignments but the rest of the assignments contained unsatisfactory use of modal verbs and conditional clauses to present arguments and connectors to show sequence of steps in assignments requiring explanations.